Neostatin-7 Regulates bFGF-induced Corneal Lymphangiogenesis - Kojima, Takashi (2008)
Neostatin-7, with an anti-angiogenic potential, is generated from the proteolytic action of matrix metalloproteinase-7 on collagen XVIII. We previously reported that neostatin-7 inhibited angiogenesis in vitro and in vivo. Here we demonstrate that neostatin-7/collagen XVIII may possess anti-lymphangiogenic activities by: 1) corneal micropellet implantation of neostatin-7 reduced bFGF-induced corneal lymphangiogenesis; 2) neostatin-7 bound to VEGF receptor-3 in vitro; and 3) enhanced corneal lymphangiogenesis and VEGF-C expression in collagen XVIII knockout mice in a corneal wounding model. Understanding the mechanism of neostatin-7/collagen XVIII on corneal lymphangiogenesis may provide therapeutic interventions to treat lymphangiogenesis-related disorders, such as lymphedema, transplantation rejection and cancers.